ANALISIS PRAGMATIK DAN DIKSI PUISI “PADA SUATU PAGI HARI” KARYA SAPARDI DJOKO DAMONO - Yusliawati Yusliawati; Eka Nur Rachmawati; Mekar Ismayani (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2019)
In this study based on curiosity to analyze the meaning contained in the sentence between sentences and diction contained in the poem "Pada Suatu Pagi Hari". The researcher formulates the problem as follows (1) to analyze the pragmatics and diction of the poem "Pada Suatu Pagi Hari", (2) to describe the sentence poem between sentences, denotation meaning, and connotation meaning. The purpose of analyzing on the part of the pragmatic meaning of the verse poem "Pada Suatu Pagi Hari"? and what is the meaning of sentence sentences between sentences? So that it aims to discuss (1) to analyze the pragmatic poem "Pada Suatu Pagi Hari". (2) to describe sentence poetry between sentences, denotation meanings and connotation meanings, as well as intrinsic elements. This study uses descriptive qualitative methods, this method is a research method that examines and discusses aspects of word choice by ensuring the contents of the poem to the denotation and connotation meanings. In the results of the analysis, there are seven types of meanings between sentences. Denotation meanings are listed in five types of sentence meanings, while connotation meanings are listed in two types of sentence meanings.